Strain gradient elasticity within the symmetric BEM formulation - S. Terravecchia; T. Panzeca; C. Polizzotto (Fracture and Structural Integrity)
The symmetric Galerkin Boundary Element Method is used to address a class of strain gradient elastic materials featured by a free energy function of the (classical) strain and of its (first) gradient. With respect to the classical elasticity, additional response variables intervene, such as the normal derivative of the displacements on the boundary, and the work-coniugate double tractions. The fundamental solutions - featuring a fourth order partial differential equations (PDEs) system - exhibit singularities which in 2D may be of the order 1/ r 4 . New techniques are developed, which allow the elimination of most of the latter singularities. The present paper has to be intended as a research communication wherein some results, being elaborated within a more general paper [1], are reported.